METAFORA KONSEPTUAL PADA LIRIK LAGU KARYA FIERSA BESARI DAN FEBY PUTRI - Siva Risthavania Putri; Nadiya Yunianti; Neneng Nurjanah (Jurnal Ilmiah SEMANTIKA, 2023)
This paper reviews cognitive semantics, especially the conceptual metaphors of Lakoff and Johnson's theory in the song lyrics by Fiersa Besari and Feby Putri. This study used a descriptive qualitative approach with note-taking techniques. The data sources that the authors studied were the lyrics of the song Runtuh by Fiersa Besari and Feby Putri, the lyrics of the song Komedi Tragis by Fiersa Besari, and the lyrics of the song Usik by Feby Putri. The purpose of this writing is to describe the conceptual metaphor in the lyrics of the song by Fiersa Besari and Feby Putri. The results of the discussion that the authors found in this study were 12 conceptual metaphors from Lakoff and Johnson's theory consisting of 6 structural metaphors, 1 orientational metaphors, and 5 ontological metaphors. Hopefully the results of the discussion that the author examines can help readers in studying the conceptual metaphors of Lakoff and Johnson's theory.